2017
DOI: 10.1109/jbhi.2015.2497717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AllergiSense Smartphone Tools for Adrenaline Injection Training

Abstract: Abstract--Anaphylaxis is an increasingly prevalent lifethreatening allergic condition that requires people with anaphylaxis and their caregivers to be trained in the avoidance of allergen triggers and in the administration of adrenaline autoinjectors. The prompt and correct administration of autoinjectors in the event of an anaphylactic reaction is a significant challenge in the management of anaphylaxis. Unfortunately, many people do not know how to use auto-injectors and either fail to use them or fail to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Very few apps had been clinically validated and many were not based on guidelines or clinical evidence. Since then, various studies have evaluated the advantages, usability, efficiency, and risks of mobile health technologies in allergic rhinitis, asthma, atopic dermatitis, food allergy, and anaphylaxis …”
Section: Becoming Wireless—the Frantic Evolution Of Information and Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few apps had been clinically validated and many were not based on guidelines or clinical evidence. Since then, various studies have evaluated the advantages, usability, efficiency, and risks of mobile health technologies in allergic rhinitis, asthma, atopic dermatitis, food allergy, and anaphylaxis …”
Section: Becoming Wireless—the Frantic Evolution Of Information and Cmentioning
confidence: 99%
“…This can be used as a base for warning systems of potentially dangerous insects. Moreover, mHealth can serve to communicate with emergency departments or authorities in isolated regions or when no help is present in case of a potentially severe allergic reaction . mHealth also might help to record and identify the culprit insect after a stinging event.…”
Section: Mhealth In Allergic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, managing the medication can be burdensome, and people often do not have experiences with injections. To support better training with adrenaline injection in an emergency, Hernandez-Munoz and colleagues designed AllergieSense that provides step-by-step training with sensors detecting injection procedures [43]. In a two-week deployment, they found that training with sensing support improved injection training skills and individual self-efficacy.…”
Section: Technologies To Support the Management Of Food Hypersensitivitiesmentioning
confidence: 99%
“…In addition, Davidson et al (2017) explored React, a mobile application which used video-based anaphylaxis narratives to illustrate to young people how different selfmanagement choices may have different consequences. Similarly, Hernandez-Munoz et al (2017) presents AllergieSense, a smartphone application and sensing system for emergency preparedness to manage anaphylaxis reactions. It includes a list of videos about anaphylaxis and symptoms which provide important information to the user in a convenient manner.…”
Section: Related Workmentioning
confidence: 99%